Gobiernos locales y Mercosur - Huerto Romero, María (Universidad del Rosario, 2017)
In recent years, we have witnessed an increasing involvement of cities in the international agenda. This phcnomcnon, while assigning a new dimension to international relationships, integrares an innovative concept to local management: cities' international scope.In cities located within Mercosur, the promotion -and, in many cases, the start up-- of their international participation has been focused on thc sub-regional space. Strategies planned to participare in the integration process and in the setting up of cities' regional networks seem to embody the mechanisms more widcly used by local governments to achieve international insertion.The purpose of this paper is to scrutinize this specific issue: thc surfacing of local power in the international relationships in the South Cone. It shall be exarnined from two different perspectives: its horizontal dimension (cooperation stratcgics and transnational alliances: Mercociudades network) and its vertical dimension (contributions to the design of common policies in the Mercosur).